If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(-1x + -10) = 10(-1x + -10) Reorder the terms: -6(-10 + -1x) = 10(-1x + -10) (-10 * -6 + -1x * -6) = 10(-1x + -10) (60 + 6x) = 10(-1x + -10) Reorder the terms: 60 + 6x = 10(-10 + -1x) 60 + 6x = (-10 * 10 + -1x * 10) 60 + 6x = (-100 + -10x) Solving 60 + 6x = -100 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 60 + 6x + 10x = -100 + -10x + 10x Combine like terms: 6x + 10x = 16x 60 + 16x = -100 + -10x + 10x Combine like terms: -10x + 10x = 0 60 + 16x = -100 + 0 60 + 16x = -100 Add '-60' to each side of the equation. 60 + -60 + 16x = -100 + -60 Combine like terms: 60 + -60 = 0 0 + 16x = -100 + -60 16x = -100 + -60 Combine like terms: -100 + -60 = -160 16x = -160 Divide each side by '16'. x = -10 Simplifying x = -10
| 8x-9x=73-82 | | 0.50x+0.15(70)=48.5 | | 35+x=18 | | -7(3a+10)=0 | | 4(w+1)=6-2(1-2w) | | y-81=-12 | | -8y+12=-28 | | 61+x=5 | | 9+8x=72+8 | | 3x-2x=-3-2x | | 19=4n+7 | | 5x+3-4x=9 | | 73-6x=30x+17 | | X-.28x=463.32 | | 2-4y=1-5y | | 3x+(2x+4)=5(x+1)+3 | | 5x+6=-69 | | -4[x-2(2x-3)]+1=x-3 | | x-(-50)=55 | | -10-8p+15+9p=2 | | 11x^2-8=432 | | 6+0.60x=13.20 | | -9+3b=12 | | 8-5q=21-2q | | 6X(2x-5)=0 | | x-(-54)=-11 | | 2y^2+10y-48= | | 9x+9+4x=39 | | Y=x^2+9x+19 | | x-62=-20 | | 7-5x=x-12 | | 2x^2-48x=0 |